Therapeutic Targeting of Tumor Cells and Tumor Immune Microenvironment Vulnerabilities - Kalyanaraman, Balaraman; Cheng, Gang; Hardy, Micael (Frontiers in Oncology, 2022)
Therapeutic targeting of tumor vulnerabilities is emerging as a key area of research. This review is focused on exploiting the vulnerabilities of tumor cells and the immune cells in the tumor immune microenvironment (TIME), including tumor hypoxia, tumor acidity, the bidirectional proton-coupled monocarboxylate transporters (MCTs) of lactate, mitochondrial oxidative phosphorylation (OXPHOS), and redox enzymes in the tricarboxylic acid cycle. Cancer cells use glucose for energy even under normoxic conditions. Although cancer cells predominantly rely on glycolysis, many have fully functional mitochondria, suggesting that mitochondria are a vulnerable target organelle in cancer cells. Thus, one key distinction between cancer and normal cell metabolism is metabolic reprogramming. Mitochondria-targeted small molecule inhibitors of OXPHOS inhibit tumor proliferation and growth. Another hallmark of cancer is extracellular acidification due lactate accumulation. Emerging results show that lactate acts as a fuel for mitochondrial metabolism and supports tumor proliferation and growth. Metabolic reprogramming occurs in glycolysis-deficient tumor phenotypes and in kinase-targeted, drug-resistant cancers overexpressing OXPHOS genes. Glycolytic cancer cells located away from the vasculature overexpress MCT4 transporter to prevent overacidification by exporting lactate, and the oxidative cancer cells located near the vasculature express MCT1 transporter to provide energy through incorporation of lactate into the tricarboxylic acid cycle. MCTs are, therefore, a vulnerable target in cancer metabolism. MCT inhibitors exert synthetic lethality in combination with metformin, a weak inhibitor of OXPHOS, in cancer cells. Simultaneously targeting multiple vulnerabilities within mitochondria shows synergistic antiproliferative and antitumor effects. Developing tumor-selective, small molecule inhibitors of OXPHOS with a high therapeutic index is critical to fully exploiting the mitochondrial vulnerabilities. We and others developed small-molecule inhibitors containing triphenylphosphonium cation that potently inhibit OXPHOS in tumor cells and tissues. Factors affecting tumor cell vulnerabilities also impact immune cells in the TIME. Glycolytic tumor cells supply lactate to the tumor-suppressing regulatory T cells overexpressing MCTs. Therapeutic opportunities for targeting vulnerabilities in tumor cells and the TIME, as well as the implications on cancer health disparities and cancer treatment, are addressed.